(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
Although it hosts silent films, Calimero episodes and MTV music videos, YouTube is often described as a “generational medium”. This is essentially due to the importance covered by the figure of the “YouTuber”, the person capable of inhabiting the semantic field constructed by the dispositif with the greatest relevance and ease. But what are his/her true generational traits? Have they to do with age, with a posture, with the objects of his/ her videos? In this article I want to study the problematic crucial nodes of this relation between YouTube as apparatus and the concept of generation.